SA Metal Group : could bigger be better? - Metton, Eulalie; Sieff, Grant ([London] : SAGE, 2016)
SA Metal Group is a growing family business based in Epping, Cape Town. In 2001, the company had expanded to Gauteng, and its operations there were fast exceeding expectations. However, the questions facing SA Metal Group's continuing expansion were multifaceted, given the high standards achieved by SA Metal in the Cape. This text examines SA Metal's transition from medium to large in size in an increasingly competitive national and international market.
Originally Published in: Metton, E., & Sieff, G. (2011). SA Metal Group: Could Bigger Be Better? WBS-2011-3. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; SA Metal Group; Family-owned business enterprises -- Case studies; Corporations -- Growth -- Case studies; Business enterprises -- Size -- Case studies; Corporate governance -- Case studies